Differences between Roma and non-Roma in how social support from family and friends helps to overcome health care accessibility problems - Bobakova, Daniela; Dankulincova Veselska, Zuzana; Babinska, Ingrid; Klein, Daniel; Madarasova Geckova, Andrea; Cislakova, Lydia; HEPA-META team (International journal for equity in health, 2015)
BACKGROUND: Roma are the most deprived ethnic minority in Slovakia, suffering from discrimination, poverty and social exclusion. Problematic access to good quality health care as result of institutional and interpersonal discrimination affects their health; therefore, factors which affect health care accessibility of Roma are of high importance for public health and policy makers. The aim of this study was to explore the association between health care accessibility problems and ethnicity and how different levels of social support from family and friends affect this association. METHODS: We used data from the cross-sectional HepaMeta study conducted in 2011 in Slovakia. The final sample comprised 452 Roma (mean age = 34.7; 35.2% men) and 403 (mean age = 33.5; 45.9% men) non-Roma respondents. RESULTS: Roma in comparison with non-Roma have a more than 3-times higher chance of reporting health care accessibility problems. Social support from family and friends significantly decreases the likelihood of reporting health care accessibility problems in both Roma and non-Roma, while the family seems to be the more important factor. CONCLUSION: The worse access to health care of Roma living in so-called settlements seems to be partially mediated by social support. Interventions should focus on Roma health mediators and community workers who can identify influential individuals who are able to change a community's fear and distrust and persuade and teach Roma to seek and appropriately use health care services.
Keywords: Interviews as Topic; Cross-Sectional Studies; Family; Health Services Accessibility; přátelé; Friends; mladiství; Middle Aged; mužské pohlaví; dostupnost zdravotnických služeb; průřezové studie; Adult; mladý dospělý; Romové; kvalitativní výzkum; Slovakia; Slovenská republika; Young Adult; Qualitative Research; ženské pohlaví; Humans; sociální opora; Social Support; lidé středního věku; rozhovory jako téma; Roma; dospělí; rodina; Female; Adolescent; lidé; Male